Patterns of invasive mechanical ventilation in patients with severe blunt chest trauma and lung contusion: A French multicentric evaluation of practices. (February 2019) - Prunet, Bertrand; Bourenne, Jérémy; David, Jean-Stéphane; Bouzat, Pierre; Boutonnet, Mathieu; Cordier, Pierre-Yves; Renaudin, Pierre; Meaudre, Eric; Michelet, Pierre
Introduction: This study investigated invasive mechanical ventilation modalities used in severe blunt chest trauma patients with pulmonary contusion. Occurrence, risk factors, and outcomes of early onset acute respiratory distress syndrome were also evaluated. Methods: We performed a retrospective multicenter observational study including 115 adult patients hospitalized in six level 1 trauma intensive care units between April and September of 2014. Independent predictors of early onset acute respiratory distress syndrome were determined by multiple logistic regression analysis based on clinical characteristics and initial management. Results: Protective ventilation principles were highly implemented, even prophylactically before acute respiratory distress syndrome occurrence. Early onset acute respiratory distress syndrome appeared to be associated with lung contusion of >20% of total lung volume and early onset pneumonia. Conclusions: Predictors of early onset acute respiratory distress syndrome could help with identifying high-risk populations, potentially improving case management through specific protocol development for these patients.